Expression of inhibitors of apoptosis proteins in salivary gland adenoid cystic carcinoma: XIAP is an independent marker of impaired cause‐specific survival. (5th February 2020) - Schnoell, Julia; Kadletz, Lorenz; Jank, Bernhard J.; Oberndorfer, Felicitas; Brkic, Faris F.; Gurnhofer, Elisabeth; Cede, Julia; Seemann, Rudolf; Kenner, Lukas; Heiduschka, Gregor
Abstract: Objectives: Inhibitors of apoptosis proteins are crucial to carcinogenesis since their expression results in evasion of apoptosis. Overexpression of inhibitors of apoptosis has repeatedly been associated with resistance to treatment and poor prognosis in various cancers. The role of inhibitors of apoptosis in adenoid cystic carcinoma of the salivary gland is still unclear. The aim of this study was to investigate the expression of inhibitors of apoptosis and their potential prognostic value in adenoid cystic carcinoma. Design, setting and participants: Forty‐nine patients, diagnosed with adenoid cystic carcinoma of the salivary gland between 1996 and 2016, were retrospectively included in this study. The expression of cIAP1, cIAP2, XIAP, Birc6, Livin and Survivin was assessed using immunohistochemistry, and their association of survival and prognosis was evaluated during a median follow‐up of 6.4 years. Main outcome measure: Cause‐specific survival and recurrence‐free survival rates. Results: XIAP, cIAP2, Livin and nuclear Survivin showed high expression levels in adenoid cystic carcinoma in most patients. There was no significant association of cIAP1, cIAP2, Livin, Birc6 and Survivin with outcome. However, high XIAP expression was associated with worse cause‐specific survival and worse response to radiotherapy and proved to be an independent marker in multivariable analysis. Conclusion: Our data indicate that high expression of XIAP may be used as a prognosticator for poor survival and poor response to radiotherapy in adenoid cystic carcinoma patients.